PV-MBLL algorithm for extraction of absolute tissue oxygenation information by diffuse optical spectroscopy. (September 2020) - Bai, Jing; Zhu, Qisen; Liu, Yinqiu; Zhou, Yihang; Shi, Tianlei; Gui, Zhiguo; Shang, Yu
Highlights: A novel algorithm to extract absolute tissue oxygenation with continuous-wave light. First attempt for oxygenation measurement with single source-detector optical signals. Verified on tissue-mimic phantom to have advantages over conventional algorithm. Translational to human experiments for assessment of absolute tissue oxygenation. Highly appropriate for the tissues with small size and large curvature. Abstract: Background and objective: Tissue blood oxygenation contains critical information for biomedical studies and healthcare. The primary approach to extract the absolute value of tissue blood oxygenation (e.g., oxygen saturation) is spatial-resolved algorithm for near-infrared diffuse optical spectroscopy with continues-wave (CW) light, which require acquisition of the optical signals from multiple pairs of sources and detectors (S-D). This study reports the first attempt for absolute oxygenation measurement with single S-D pair of optical signals. Methods: A novel algorithm, namely, phantom-validation modified Beer-Lambert law (PV-MBLL), was created to fully utilize the optical signals from single S-D pair. This algorithm is combined with two-step phantom measurement to extract the absolute value of tissue oxygenation in CW system. The proposed PV-MBLL algorithm was compared with the conventional spatial-resolved algorithm on both step-varied liquid phantom and human experiment of cuff occlusion on arms. The one-way ANOVA analysis was performed to investigate the difference between the two algorithms. Results: By using the PV-MBLL algorithm, the reconstructed tissue absorption coefficient is highly accurate (not larger than 5.35% in error) over a wide range (0.02–0.20 cm −1 ). By contrast, the spatial-resolved algorithm leads to much larger errors (up to 37.57% in error). Moreover, the responses of oxygen saturation to cuff occlusion differ significantly ( p  < 0.005) with the two algorithms. Conclusions: The proposed PV-MBLL algorithm has promising potential for accurate acquisition of oxygenation information. Additionally, the single S-D pair greatly reduces the size of optical probe and instrument cost, thus it is highly appropriate for the tissues with small size and large curvature.